Shoulder blade resection - Valls, Alberto; Cardenia, Julio C. (Cirugía del Uruguay, 1974)
By reason of an extensive scapula resection, due to a metastasis of a kidney's cancer, the authors report the techniques of the scapula resections. By means of an incision that separa tes cutaneous nervous territories, opening the triangular covering formed by the deltoid muscles in the outside, the trapezius in the inside and upper parts and the latissimus dorsi downwards. Sectioning the rhomboideus and the (angular), the scapular unit is moved as a fan with an extern handle in the humerus upper end. Afterwards the scapular muscles are sectioned to allow the extirpation of the scapula. In the total resection, the humerus is fixed to the. clavicle, the covering muscles and the skin aresutured leaving a drainage. In the resections that keep the (glena) untouched, the functional recuperation is very good.